Math, asked by pvinodjet, 1 year ago

solve by equating the coefficients for x and y: 3x +2y +1=0, 2x-3y +8=0​

Answers

Answered by arnav1232
4

first is 3x + 2y = -1

next is 2x - 3y =-8

Now multiply first by 3 and second eq by 2 to equate coefficients of y

so we get 9x + 6y = -3

               +4x - 6y = -16

               -----------------------

               13x         =-19

hence x = -19/13

subsequently y = -17/13

PLZ MARK ME AS THE BRAINLIEST!!

Answered by princesaini1298
2

Answer:

Step-by-step explanation:bhai google se dekhle

Similar questions